Trinibaculum altiparanae sp. n. a new dactylogyrid species (Monogenea) of the Astyanax altiparanae (Osteichthyes: Characidae) in the Peixe River, Southeastern Brazil - Abdallah, Vanessa Doro; Azevedo, Rodney Koslowiski de; Silva, Reinaldo José da [UNESP] (My University, 2013)
This article describes a new species –Trinibaculum altiparanae sp. n. –found in the gills of the Astyanax altiparanae Garutti & Britski, 2000. Fish were collected from the Peixe River in the municipality of Anhembi, State of São Paulo, Brazil, in March 2010. This paper describes the third species of the genus Trinibaculum. This new species is characterized by having an accessory structure that does not articulate with the male copulatory organ (MCO). This accessory structure has a basally bifid, well-curved distal end, tapered with a terminal flabellate piece. The male copulatory organ is a simple tube with less than one ring coiled counterclockwise; two similar curved dorsal bars; a ventral bar with concave ends and a posterior projection, a dorsal anchor with a truncated deep root and a slightly curved shaft, a ventral anchor with a curved shaft and differently shaped and sized hooks. Those features distinguish the new species from the two other species previously described in this genus: Trinibaculum braziliensis Kritsky, Thatcher & Kayton, 1980 was found parasitizing Brycon melanopterus (Cope, 1872) and Trinibaculum rotundus Karling, Lopes, Takemoto & Pavanelli, 2011 was found parasitizing Schizodon borellii (Boulenger, 1900).

Una nueva especie - Trinibaculum altiparanae sp. n. - se describe de las branquias de Astyanax altiparanae Garutti & Britski, 2000. Los peces fueron recolectados en el río Peixe en el municipio de Anhembi, São Paulo, Brasil, en marzo del 2010. Esta es la tercera especie del género Trinibaculum que se describe. La nueva especie se caracteriza por tener una pieza accesoria no articulada al órgano masculino copulador (COM), basalmente bífida y curva, el extremo distal cónico con una pieza terminal flabelada. El órgano copulador masculino es un tubo simple y envuelto con menos de una vuelta en dirección hacia la izquierda; barras dorsales similares y curvadas; una barra ventral con extremo cóncavo y con proyección posterior; raíz del áncora dorsal profunda y truncada y suavemente curvada; áncora ventral curvada y ganchos con diferente forma y tamaño, que difiere de las otras dos especies previamente descritas en este género: Trinibaculum braziliensis Kritsky, Thatcher & Kayton, 1980 que parasita a Brycon melanopterus (Cope, 1872) y Trinibaculum rotundus Karling, Lopes, Takemoto & Pavanelli, 2011 que parasita Schizodon borellii(Boulenger, 1900).
Trinibaculum altiparanae sp. n. una nueva especie de dactylogyrido (Monogenea) de Astyanax altiparanae (Osteichthyes: Characidae) en el río Peixe, sudeste de Brasil
Keywords: Ancyrocephalinae; Astyanax altiparanae; Monogeneans; State of São Paulo; Trinibaculum altiparanae sp. n.; Ancyrocephalinae; Astyanax altiparanae; Estado de São Paulo; Monogeneos; Trinibaculum altiparanae sp. n.